Fish bone foreign body causing rectal, uterine, and bladder perforation: a rare case report - Luo, Shiyu; Gou, Bo; Zeng, Tengyu; Liu, Jian; Li, Jun; Zhou, Jiangying (Frontiers in Oncology, 2026)
Fish bones are one of the most common gastrointestinal foreign bodies resulting from accidental ingestion. While the majority can pass through the gastrointestinal tract via peristalsis, a small proportion may become lodged in the digestive tract, potentially causing injury to the gastrointestinal wall or adjacent tissues. However, visceral perforation remains extremely rare. Preoperative abdominal imaging examinations provide crucial evidence for the diagnosis and localization of fish bone foreign bodies. This article reports a case of a patient presenting with painless hematuria who was initially suspected to have malignant bladder lesions. Through multimodal joint analysis, the diagnosis of foreign body-induced bladder perforation was established, which was subsequently confirmed by Collaborative Laparoscopic Therapy to be caused by a fish bone perforating the rectum, uterine isthmus serosa, and bladder, accompanied by the formation of surrounding inflammatory granulation tissue. Due to the extreme rarity of fish bones becoming lodged in the lower gastrointestinal tract and causing perforation of multiple organs, this case is being reported.